Dzielimy Się DoświadczeniamiSurgical ablation for atrial fibrillation through atrial septal defect during typical correction of the defect - Suwalski, Piotr; Pawlak, Szymon; Gburek, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Atrial fibrillation (AF) is the most frequent clinically important arrhythmia, being a significant risk factor for thromboembolism, deterioration of left ventricle function and mortality. This arrhythmia has an impact on long term survival and mortality in patients after cardiac surgery. Recent years have revealed rapid development in terms of technology and electrophysiology of AF. Surgical ablation of AF is becoming a frequently performed procedure, usually in operations where opening of the left atrium is necessary. We describe a patient with atrial septal defect in whom surgical ablation of the left atrium with approach through the defect was performed.